Humus and Humic Acids of Luvisol and Cambisol of Jiguli Ridges, Samara Region, Russia - Evgeny Abakumov; Nobihudu Fujitake; Takashi Kosaki (Applied and Environmental Soil Science)
Luvisols and Cambisols are two types of sub-boreal soils, which are known as continental and humid-ocean types of soils in deciduous forests respectively. Morphological features of soil, which are frequently used as the main argument in solum diagnostics, are subjective and do not give final decision that continental Cambisols are a specific type of soils different from Luvisols. These soils were studied in a mountain massive—Jiguli ridges of Samara region, Russia, East European part. Humid climate of northern slopes leads to formation of brown type of humic acids (HA), while the conditions of eastern slopes assist to formation of gray HA. These HAs of different soils are different in elemental composition (C and N are higher in Cambisols, O is higher in Luvisols), carbon species according to 13-C NMR (aromaticity is higher in Luvisols, while the aliphatic, carbonylic and carboxylic compounds are higher in Cambisols). Cambisols are characterized by dominance of fulvic acids (FAs) on HAs, while the ratio of HA to FA groups in Luvisols is about 1,0. Essential differences in humus composition and humic acids properties confirm that local humid climate in continental forest-steppe leads to formation of Cambisols instead of zonal Luvisols.